The Global Challenge of Human Rights and Solidarity to Nordic Global Companies and Trade Unions - Schiller, Bernt (Nordic Journal of Working Life Studies, 2014)
The idea that corporations, besides making profit, have a social responsibility to society is not new in history. Nor is it new that unions besides representing material interests stand for a universal ambition as defenders of the oppressed in the world. The article argues that corporations’ social responsibility and trade union solidarity, to the extent both are based on universal principles of human rights, ought to open for cooperation concerning Corporate Social Responsibility (CSR), where trade unions should be recognized as important stakeholders in corporations. This idea is new, even if examples exist, and it challenges traditional concepts of the role of management and unions in the company. However, trade unions have taken a critical attitude to CSR, the implementation of which they have mainly been excluded from. Instead, they have tried to get global agreements, Global Framework Agreements (GFAs), with the MNCs.1 In the article the development of the attitudes of the International Trade Union Confederation (ITUC) and of the Nordic national centers is investigated. A long-term historical perspective, in addition to a general theory of collective action will be used to draft the hypothesis that, when unions as interest organizations, through the process of national integration, have achieved a strong position in the domestic labor market, they lack reasons to take transnational action and seek international trade union solidarity. This hypothesis is valid today for the well-established unions in the Nordic countries. But in questions concerning social responsibility and human rights, the article presents the possibility that GFAs might become a platform from which to extend the Nordic model of national partnership to the global level, while at the same time global competition will increasingly make it difficult for the unions to show international solidarity in interest questions of capital investments and outsourcing.